2021
DOI: 10.3390/en14020382
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Gain Super-Twisting Sliding Mode Damping Control of Series-Compensated DFIG-Based Wind Power System for SSCI Mitigation

Abstract: Subsynchronous oscillation, caused by the interaction between the rotor side converter (RSC) control of the doubly fed induction generator (DFIG) and series-compensated transmission line, is an alleged subsynchronous control interaction (SSCI). SSCI can cause DFIGs to go offline and crowbar circuit breakdown, and then deteriorate power system stability. This paper proposes a novel adaptive super-twisting sliding mode SSCI mitigation method for series-compensated DFIG-based wind power systems. Rotor currents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Table 2 shows the predicted results of power load on working days. In the analysis, the complete power load data of the grid for 100 consecutive working days (excluding weekends) were selected [19]. From the prediction results, the prediction results of random forest and the LSTM algorithm are relatively close, more accurate than the SVM but not as good as the authors' method.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the predicted results of power load on working days. In the analysis, the complete power load data of the grid for 100 consecutive working days (excluding weekends) were selected [19]. From the prediction results, the prediction results of random forest and the LSTM algorithm are relatively close, more accurate than the SVM but not as good as the authors' method.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [80] investigated the SSCI in DFIG based wind farms using the Eigenvalue analysis method. [81] proposed the reactance crossover-based technique (RCT) to investigate SSCI in the DFIG system using ERCOT real grid scenarios as a case study.More recent studies regarding the SSCI can be found in [82][83][84][85][86][87][88][89].…”
Section: Sscimentioning
confidence: 99%
“…The paper authored by Philippe Enrici, Ivan Meny and Daniel Matt, studied a low-power wind system based on a perma-nent magnet Vernier machine, in association with a PWM rectifier, with a diode bridge rectifier [5]. The second paper [6], authored by Ronglin Ma, Yaozhen Han and Weigang Pan, proposes a novel adaptive super-twisting sliding mode subsynchronous control interaction mitigation method, for series-compensated doubly fed induction generatorbased wind power systems. The last paper, authored by Gianluca Brando, Adolfo Dannier and Ivan Spina, analyzes the performance of a full order sensorless control adaptive observer, for a doubly fed induction generator, in the grid-connected operation of a turbine-based wind generation system [7].…”
Section: Power Converter Of Electric Machines Renewable Energy Systems and Transportationmentioning
confidence: 99%